Transcriptomic Profiling of Human Placenta in Gestational Diabetes Mellitus at the Single-Cell Level - Yang, Yuqi; Guo, Fang; Peng, Yue; Chen, Rong; Zhou, Wenbo; Wang, Huihui; OuYang, Jun; Yu, Bin; Xu, Zhengfeng (Frontiers in Endocrinology, 2021)
Gestational diabetes mellitus (GDM) is associated with an increased risk of adverse pregnancy outcomes. Increasing evidence shows that placentation defects may play important roles in GDM. However, our understanding of the human placenta remains limited. In this study, we generated a comprehensive transcriptomic profile of cellular signatures and transcriptomes in the human placenta in GDM using single-cell RNA sequencing (scRNA-seq), constructed a comprehensive cell atlas, and identified cell subtypes and subtype-specific marker genes. In addition, we investigated the placental cellular function and intercellular interactions in GDM. These findings help to elucidate the molecular mechanisms of GDM, and may facilitate the development of new approaches to GDM treatment and prevention.